ANALISIS YURIDIS PENGGUNAAN CESSIE UNTUK PENGAJUAN KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) DENGAN 1 (SATU) KREDITOR (STUDI KASUS TERHADAP PUTUSAN PENGADILAN NIAGA NOMOR 63/PKPU/2012/PN.NIAGA. JKT.PST. DAN PUTUSAN PENGADILAN NIAGA NOMOR 09/PAILIT/ - Novalia Simamora; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
PKPU decision No. 63/ PKPU / 2012 / PN.Niaga.Jkt.Pst, the judge in its verdictacknowledges that the transfer of receivables (cessie) made by PT.Global (the applicant) toJohanes H.L.Thomas, although not preceded by civil events. Decision No. 09 / Bankrupt /2013 / PN.Niaga.Mdn, rejected the petition for bankruptcy filed by the petitioner because thejudge believes that the Cessie done by PT.TUM (the applicant) to Maswadi Yanto Ndey isconsidered invalid because it was not preceded by civil events prior to the transition accountsreceivable (cessie).The purpose of this research is first, to know whether to file Bankruptcy andSuspension of Payment Obligation (PKPU) with 1 (one) creditor. Second, how to obtainother creditors by using available legal institutions and tools and lastly to see if the cessiehas the legal power to get other creditors.This research uses the method used is normative juridical. This research method isdone by examining the existing library material that is more discussed about legalsystematics. The data used is secondary data, that is data supporting the information orsupporting the completeness of primary data obtained from library conducted by literaturestudy or literature. Data collection techniques that will be used in this research is by way oflibrary research and data analysis is done qualitatively normative ie the analysis usedwithout the use of numbers and statistics and mathematical formulation is presented in theform of description.The results of this research are first, based on Article 2 paragraph (1) of Law Number37 Year 2004 on Bankruptcy and Postponement of Debt Payment Obligations. The creditorcan not apply for Bankruptcy and Suspension of Debt Payment Obligation because it doesnot meet one of the requirements that the debtor has only 1 creditor only. Secondly, Cessie isa method of transferring and / or handling of receivables in the name set forth in Article 613of the Civil Code (KUH Perdata). The transition of receivables by means of this cessie thatcan be used as a creditor to get other creditors. Third, the government should make morespecific and detailed legal rules on the transfer of receivables in a cessie manner so that lawenforcement authorities can consistently apply the rule of law for the sake of justice for theparties concerned in PKPU.Keywords: Cessie-Bankruptcy-Legal Certainty